2014
DOI: 10.1155/2014/746192
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation in Systemic Lupus Erythematosus: Outcome and Prognostic Factors in 50 Cases from a Single Centre

Abstract: Background. End-stage renal disease (ESRD) is an important cause of morbidity and mortality in patients with systemic lupus erythematosus (SLE). Objectives. To analyze the outcome and prognostic factors of renal transplantation in patients with ESRD due to SLE from January 1986 to December 2013 in a single center. Results. Fifty renal transplantations were performed in 40 SLE patients (32 female (80%), mean age at transplantation 36 ± 10.4 years). The most frequent lupus nephropathy was type IV (72.2%). Graft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 43 publications
10
20
0
Order By: Relevance
“…This is similar to recent work which found that increased time on dialysis led to increased graft failure [9, 18]. Indeed, our cohort included two patients with pre-emptive transplantation and they both remain alive at 22 and 12 years respectively, supporting that the earlier benefits of rTp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is similar to recent work which found that increased time on dialysis led to increased graft failure [9, 18]. Indeed, our cohort included two patients with pre-emptive transplantation and they both remain alive at 22 and 12 years respectively, supporting that the earlier benefits of rTp.…”
Section: Discussionsupporting
confidence: 90%
“…However, in the early era of renal transplantation, lupus patients were considered unfavourable candidates given an assumed risk of recurrent LN. Since 1975, however, when it was first suggested that the outcomes of transplant in SLE are comparable to non-SLE patients [5], there have been reports across the globe and in different ethnic populations that have shown low recurrence rates of LN in kidney transplant recipients [69]. Some studies, however, have raised concern regarding worse graft and patient survival of SLE patients when compared to other patient groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most of our patients with RLN received living donor transplantation. Previous studies reported controversial findings about relation between donor type and risk of recurrence and graft failure . Norby et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported living donor transplantation as a risk factor for RLN while Cairoli et al . reported deceased KTx as a risk factor for graft failure . Serological markers of SLE are strongly related with lupus activity in native kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed SLE adversely affects the transplant outcome, (8-10) whilst others did not support this. [11][12][13][14][15][16] The largest retrospective study usingUnited StatesRenalData System (USRD) and United Network for Organ Sharing(UNOS) databases showed transplantation in SLE had inferior graft and recipient outcome compared with diabetic ESRD patients. 17 One important consideration regarding SLE is that it might create obstacle from getting CDC cross-match negative donor and render them on long waiting list 18 as in this case, which would have definite adverse prognostic impact on transplant outcome.…”
Section: Discussion Of the Casementioning
confidence: 99%